Change in body composition assessed by computed tomography in long-term survivors after esophageal cancer surgery. Issue 3 (2016) - Nakaya, Yutaka; Yuasa, Masao; Atsumi, Kana; Furukita, Yoshihito; Tangoku, Akira; Tsutsumi, Rie; Harada, Nagakatsu; Sakaue, Hiroshi
No abstract available